Exploring the inclusion of nature of science in biology curriculum and high-stakes assessments in Hong Kong - Cheung, KKC (Springer Nature, 2020)
Nature of science (NOS) has become one of the major emphases in curriculum and assessment. This study explores what NOS is included and how this is achieved in the Hong Kong biology curriculum and 7-year high-stakes assessments. While conceptualizations of the official definition of NOS differ, this study employs the family resemblance approach (FRA) to analyze the inclusion of NOS in the curriculum and the high-stakes assessments. In one characterisation of FRA (i.e. Erduran and Dagher 2014), NOS comprises a cognitive-epistemic system and a social-institutional system. There is a total of 11 categories in these two systems and these categories are interconnected with one another. By adopting the epistemic network analysis (ENA), the frequency of connections among these NOS categories in the curriculum and the high-stakes assessments can be visualized and compared. Two main similarities are observed when comparing the epistemic networks of the curriculum and the high-stakes assessments: (1) a greater emphasis on the cognitive-epistemic rather than the social-institutional system and (2) the rarity of connections between categories in the social-institutional system. However, the high-stakes assessments differ from the curriculum in that they have more connections between the cognitive-epistemic system and the social-institutional system. Moreover, assessment items in the Hong Kong biology examinations involve a limited range of contexts and skills. Implications for the design of curricula and high-stakes assessments will be discussed.